2005
DOI: 10.1128/jcm.43.12.5950-5956.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Human Immunodeficiency Virus (HIV) RNA Surrogate Assays to the Standard HIV RNA Assay

Abstract: Human immunodeficiency virus (HIV) RNA testing is the gold standard for monitoring antiretroviral therapy in HIV-infected patients. However, equipment and reagent costs preclude widespread use of the assay in resource-limited settings. The Perkin-Elmer Ultrasensitive p24 assay and the Cavidi Exavir Load assay both offer potentially simpler, less costly technologies for monitoring viral load. These assays were compared to the Roche Amplicor HIV-1 Monitor Test, v1.5, using panels of clinical samples (subtype B) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 37 publications
8
39
0
Order By: Relevance
“…CRF02_AG is the major driver of HIV infection in Ghana and others in minor proportion of circulation such as CRF06_cpx, sub-subtype A3, CRF09_cpx and subtypes A, G and D had been identified. Studies have shown that RT activity is independent of the HIV-subtype [40][41][42][43][44][45]. This is in agreement with other studies that evaluated an in-house real-time RT-PCR assay that targeted the same Long Terminal Repeat (LTR) region probing for viral RNA.…”
Section: Discussionsupporting
confidence: 80%
“…CRF02_AG is the major driver of HIV infection in Ghana and others in minor proportion of circulation such as CRF06_cpx, sub-subtype A3, CRF09_cpx and subtypes A, G and D had been identified. Studies have shown that RT activity is independent of the HIV-subtype [40][41][42][43][44][45]. This is in agreement with other studies that evaluated an in-house real-time RT-PCR assay that targeted the same Long Terminal Repeat (LTR) region probing for viral RNA.…”
Section: Discussionsupporting
confidence: 80%
“…The results of this protein-detection method were highly reproducible, regardless of the approach used to quantify the barcode DNA. Conventional enzyme immunoassays that are accepted and comparable clinically for detecting the same target have sensitivity limits of approximately 5 pg/ml (~0.2 pM), an order of magnitude less sensitive [9,29].…”
Section: Resultsmentioning
confidence: 99%
“…The model assumes that all the HIV-1 p24 Gag protein in peripheral blood is in intact virions and a mature virus core contains 1000-1500 p24 Gag proteins [9,35]. The accuracy of the ratio of p24 Gag protein to viral genomic RNA is limited by the inaccuracy in the empirical determination of the amount of HIV-1 p24 Gag sufficient for mature-virus particle assembly and is confounded by the presence of HIV-1 p24 Gag in defective or immature virus particles and residual circulating immune complexes, degraded virus particles entangled in the follicular dendritic-cell network in lymphoid tissue and HIV-1 p24 Gag released from productively infected cells or leaked from cells killed by viral or immune-mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general consensus from the meeting was that assays should include simple specimen collection methods, use nonrefrigerated reagents, cost under $8 per data point, consist of benchtop or handheld instrumentation priced under US$1000 that run on rechargeable batteries, require minimal training and generate results in less than 2 h [1]. There have been assays adapted for developing countries [105,106], but they currently fall short of these recommendations. Whereas NAT will likely remain limited to clinical and laboratory settings for the time being [107], CD4 + T -cell counting methods using flow cytometry have become simpler, easier to use, less expensive and more accessible in RLS [108,109].…”
Section: Hiv Monitoring and Managementmentioning
confidence: 99%